Ceftazidime retains in vivo efficacy against strains of Stenotrophomonas maltophilia for which traditional testing predicts resistance - Matthew C. Phillips; Bosul Lee; Sarah L. Miller; Jun Yan; Kristine Goy; Marlène Maeusli; Tina Lam; Catherine Spellberg; Michael Spellberg; Rosemary She; Brad Spellberg; Brian Luna (mSphere, 2025)
ABSTRACT Stenotrophomonas maltophilia is responsible for a growing number of nosocomial infections and is difficult to treat owing to limited antibiotic susceptibilities. However, there are numerous recently published examples where traditional susceptibility testing methodology fails to accurately predict in vivo efficacy. We sought to determine if there were efficacious antibiotics against S. maltophilia that have been overlooked due to specious in vivo resistance determined by traditional in vitro methods. Antibiotic resistance testing was performed utilizing conventional and nutrient-limited media. Antibiotics with discordant minimum inhibitory concentrations (MICs) between the two media were selected for further experimentation. Metal ions were supplemented back into the nutrient-limited media to establish possible mechanisms. In vivo corroborations of in vitro MICs were done utilizing two infection models, Galleria mellonella and a neutropenic mouse oral aspiration pneumonia model. S. maltophilia MICs were significantly lower for ceftazidime in nutritionally deficient media that better corresponds to the in vivo environment than conventional rich media, resulting in a high percentage of strains determined resistant in traditional media being determined susceptible in nutritionally deficient media. The addition of zinc and manganese to the deficient media abrogated this difference, which was dependent on the L1 metallo-β-lactamase (MBL). Ceftazidime protected both G. mellonella and neutropenic mice against lethal infection caused by S. maltophilia that was predicted to be resistant in traditional media but susceptible in nutrient-deficient media. Ceftazidime may remain a viable therapeutic option for patients with S. maltophilia infection caused by strains predicted to be resistant by traditional susceptibility testing. Sequestration of trace metals in the host environment may prevent S. maltophilia MBL activity against ceftazidime.IMPORTANCEBreakpoint interpretation criteria for ceftazidime against S. maltophilia were recently removed by CLSI and the FDA. It was noted that clinical data were insufficient to validate the current breakpoints. Clinical data were mixed, with some studies reporting treatment success, but others reporting treatment failure. We believe that antimicrobial testing is suboptimal, and improved testing strategies, such as the use of zinc-limited media for culture, will better model the activity of ceftazidime in vitro. Improved susceptibility testing strategies may better discriminate against those isolates that are truly resistant from those that were previously falsely identified as being resistant using conventional testing methods.